Expression of follicle stimulating hormone receptor variants during the sheep estrous cycle - Sullivan, Rachael R. (Kansas State University, 2009)
Several alternatively-spliced mRNA transcripts of the follicle stimulating hormone receptor (FSHR) have been identified in sheep, including FSHR-1 (G protein-coupled form), FSHR-2 (dominant negative form), and FSHR-3 (growth factor type-1 form). Coupling of the FSHR to signaling pathways which activate different downstream effectors leads to speculation that specific splice variants may be transcribed under differing physiological conditions. This is the first study to correlate expression patterns of FSHR-1, FSHR-2, and FSHR-3 and development of follicles in the mature sheep ovary. In Experiment 1, 8 Suffolk-cross ewes were allowed to come into estrus naturally and were euthanized 24 (n=3), 36 (n=3), and 48 (n=2) hours after the onset of estrus. In Experiment 2, 7 Suffolk-cross ewes received CIDRs for 14 days. At CIDR removal, PMSG (500IU) was administered to treatment ewes (n=3), while controls (n=4) received no PMSG. Ewes were euthanized 24 (n=4; 2 CIDR only, 2 PMSG) or 36 (n=3; 2 CIDR only, 1 PMSG) hours later. All visible follicles were aspirated and pooled according to follicular diameter: small (≤ 2.0 mm), medium (2.1-4.0 mm), large (4.1-6.0 mm), and preovulatory (≥ 6.1 mm). Granulosa cells were separated from follicular fluid by centrifugation. Total RNA was extracted from granulosa cells (GC) and reversed transcribed. The resulting cDNA was subjected to qPCR, using primer sets designed to amplify each variant specifically. For Experiment 1, regardless of time after onset of estrus, relative expression of FSHR-3 exceeded that of both FSHR-1 and FSHR-2 in medium follicles (p < 0.01), and tended to be higher in small follicles (p=0.09). For Experiment 2, treatment with PMSG did not significantly alter expression patterns of FSHR variants (p=0.18). The FSHR-3 was expressed higher than FSHR-2 in all follicle sizes (p < 0.01) and was numerically more highly expressed than FSHR-1, although this difference was not significant (p > 0.11). These experiments show that in addition to the well characterized G protein-coupled form of the FSHR, alternatively spliced variants of the FSHR may participate in follicular dynamics during the first follicular wave of the sheep estrous cycle. Furthermore, these results would indicate that an “alternatively” spliced form of the FSHR (FSHR-3) is the predominant form of the FSHR in the sheep.
Keywords: Follicle stimulating hormone receptor variants; Sheep; Estrous cycle; Growth factor type; Pregnant mare serum gonadotropin; Alternative splice variants; Agriculture, General (0473)